Anda di halaman 1dari 17

# 1 09-02-2008

Analysis
SYS
Input Output
u(t) y(t)
Figure 1: Block system representation.
MIMO control: u = u(t) R
m
, y(t) = y(t) R
p
Synthesis
CONTROL
u(t)
y (t)
d
SYSTEM
y(t)
Figure 2: Synthesis control system.
where:
y
d
- desired output, and we want lim
t
y
d
(t) y(t) = 0.
Classical Servo Loop Design:
COMP
u(t)
y (t)
d
SYSTEM
y(t)
e(t)
CONTROLLER
Figure 3: Feedback Controller.
In a rst course in feedback systems, we typically assumed LT I (Linear-
Time-Invariant), SISO (Single Input Single Output) systems.
y
n
(t)+
n1
y
n1
(t)+. . .+
1
y(t)+
0
y(t) =
m
u
m
(t)+. . .+
1
u(t)+
0
u(t) (1)
1
where
y(t) =
d
dt
y(t)
y(t) =
d
2
dt
2
y(t)
y
i
(t) =
d
i
dt
i
y(t)
{
i
}
n1
i=0
Real constants
{
j
}
m
j=0
Real constants
Main insight for analysis of SISO LT I systems: complex exponentials are
eigenfunctions of these systems.
Complex exponential function:
e
st
, s C
where:
s = + j = Re{s} R
= Im{s} R
NOTE: Recall j
2
= 1
Therefore:
e
st
= e
+jt
= e
t
e
jt
(2)
e
jt
= cos t + j sin t (3)
putting ?? into ??
e
st
= e
t
[cos t + j sin t] (4)
NOTES:
Components are exponentially weighted sin/cos waves: = Im{s}
frequency of oscillation.
Amplitude is time-varying: exponentially increasing/decreasing: =
Re{s} determines exponential envelope.
2
3 possible amplitude variations:
< 0 : amplitude decaying, exponentially to 0.
> 0 : amplitude diverging, exponentially to
= 0 : amplitude is constant
Complex Amplitudes
Ae
st
, s C
A C
s = + j (rectangular form)
A = re
j
(represent A in polar form)
so,
Ae
st
= re
j
e
(+j)t
(5)
= re
t
e
j(t+)
= re
t
[cos (t + ) + j sin (t + )]
where,
r = A initial amplitude
= A phase shift to oscillations.
Eigenfunctions:
Recall for a square nxn matrix A, an eigenvector v C
n
, where v = 0
satises:
Av = v for some C (6)
for a dynamical system, e
st
is an eigenfunction i:
u(t) = e
st
y(t) = e
st
for every s C and some complex number .
Fact: e
st
is an eigenfunction for an LT I system, with:
=

m
s
m
+ . . . +
1
s +
0
s
n
+
n1
s
n1
+ . . .
1
s +
0
(7)
3
PF
use:
d
dt
e
st
= se
st
d
2
dt
2
e
st
= s
2
e
st
Assume: u(t) = e
st
, y(t) = e
st
( to be determined). Then substitute into
the original dierential equation:
r(s)e
st
= q(s)e
st
where,
q(s) =
m
s
m
+ . . . +
1
s +
0
and
r(s) = s
n
+
n1
s
n1
+ . . .
1
s +
0
Thus:
e
st
=
_
q(s)
r(s)
_
e
st
*true for all time if has the for indicated //.
**By the same analysis: if u = Ae
st
, where A, s C, then y(t) = Ae
st
is a solution of the dierential equation.
suppose
u(t) 0
Q: can we have y(t) = 0
t
(YES! - pendulum released)
Q: Are these nonzero outputs still of the form e
st
?
Assume:
u(t) = 0
t
y(t) = Ce
pt
for C,p C
substitute these assumptions into the original dierential equations:
Cr(p)e
pt
= 0
t
true for any p such that r(p) = 0.
4
2 09-04-2008
e
st
, s C are eigenfunctions of a SISO LT I system.
SYS u(t) y(t)
e
st
e
st
Figure 4: Eigenfunction input-output on a linear system.
(s) =
q(s)
r(s)
where,
q(s) =
m
s
m
+ . . . +
1
s +
0
r(s) = s
n
+
n1
s
n1
+ . . . +
1
s +
0
even if, u(t) 0
t
we can have output solutions y(t) = Ce
pt
:
Cr(p)e
pt
= 0
t0
for any p such that r(p) = 0.
Consequently: p is a zero of polynomial r; where r has n such zeros p
k
,
for k = 1, . . . , n.
r(s) = (s p
1
)(s p
2
)(s p
n
)
=
n

k=1
(s p
k
)
e
p
k
t
for any p
k
which is a zero of polynomial r(s) are component solutions
which can occur even with no inputs acting on the system.
e
p
k
t
motions are intrinsic to the system dynamics; therefore, we some-
times call them the natural modes of the system.
*Note that any combination of modes is a valid zero-input solution as well.
n

k=1
c
k
r(p
k
)e
p
k
t
= 0
5
c
k
C k = 1, . . . , n
p
k
[zeros of r(s)] k = 1, . . . , n
Any combination of modes is a valid zero-input solution. Typically called
the homogenous, unforced, or free response.
y
h
= homogenous solution
more generally, when u(t) = e
st
we have solutions of the form:
y(t) = (s)e
st
. .
particularorforcedy
p
(t)
+
n

k=1
c
k
e
p
k
t
. .
y
h
(t)
Some properties of homogenous solutions. . .
Stability
|y
h
(t)| 0 as t
Then:
y(t) y
p
(t)
|e
p
k
t
| 0 as t for all k = 1, . . . , n
p
k
=
k
+ j
k

k
,
k
R
e
p
k
t
= e

k
t
e
j
k
t
|e
p
k
t
| = |e

k
t
|
| | = 1
..
|e
j
k
t
| = |e

k
t
|
stability of mode e
p
k
t
is determined by
k
= Re{p
k
}
lim
t
|e
p
k
t
| = lim
t
|e

k
t
|
therefore; the mode is stable if Re{p
k
} < 0 and the system is stable if
Re{p
k
} < 0 for all k = 1, . . . , n.
Stable modes for LT I systems decay exponentially fast, faster the more neg-
ative is
k
.
6
Unstable
RHP
Re
Im
Faster
convergence to Zero
X
Stable
LHP

k
Figure 5: Stability diagram and decay rate due to .
Re
Im

max

min

min
0
1
Lines of constant
damping ratio
Figure 6: Typical design (synthesis) constraint. Ensure Re{p
k
} <
max
for
all k = 1, . . . , n.
more generally:
e
p
k
t
= e
t
[cos
k
t + j sin
k
t]
if
k
= Im{p
k
} = 0 the mode will exhibit oscillations. Assuming the mode
is stable then the damping ratio is dened as:

k
=
|Re{p
k
}|
|p
k
|
=
|
k
|
_

2
k
+
2
k
7
for
k

= 0 mode will exhibit very pronounced oscillations
for
k

= 1 mode will exhibit negligibly observable oscillations
Typical design (synthesis) constraint ensures

k
>
min
for k = 1, . . . , n
Examination of forced component solutions
u(t) = e
st
y
p
(t) = (s)e
st
Q: can we get y
p
(t) = 0?
A: Yes if (s) = 0
(s) =
q(s)
r(s)
= 0
_
r(s) = not possible for ninite values of s
q(s) = 0
In general, q(s) = 0 has m solutions, z
i
for i = 1, . . . , m
q(s) =
m
(s z
1
)(s z
2
) . . . (s z
m
)
=
m
m

i=1
(s z
i
)
Thus:
u(t) = e
z
i
t
where z
i
is any zero of q(s) (in the steady state).
y
p
(t) = 0
Now suppose u(t) = e
st
Re{s} = 0 s = j
u(t) = e
jt
= cos t + j sin t
y
p
(t) = (j)e
jt
= M()[cos (t + ()) + j sin (t + ())]
8
where,
M() = |(j)|
() = (j)
if
u
1
(t) = Im{e
jt
} = sin t
then
y
p
1
(t) = Im{(j)e
jt
}
= M() sin (t + ())
or similarly
u
2
(t) = Re{e
jt
} = cos t
then
y
p
2
(t) = Re{(j)e
jt
}
= M() cos (t + ())
SYS
sin[t] M()sin[t+()]
Figure 7: Sinusoidal input to a linear system.
M() = |(j)|
() = (j)
We can plot amplitude M() and phase () as a function of driving fre-
quency: [0, ). This leads to the use of Bode diagrams.
Finally look at arbitrary inputs:
u(t) =
n

k=1
U
k
e
s
k
t
y
p
(t) =
n

k=1
Y
k
e
s
k
t
9
where, U
k
C, s
k
C Y
k
=
k
(s
k
)U
k
Again, by direct subsitution into the dierential equation:
y
p
(t) =
n

k=1
(s
k
)U
k
e
s
k
t
arguments hold for n . This also holds in the dierential limit, i.e.
u(t) =
_
U(s)e
st
ds
y
p
(t) =
_
Y (s)e
st
ds
Y (s) = (s)U(s) for all s C
10
09-09-2008
LTI
SYSTEM
u(t)= Ue
st
y(t)=Ye
st
U,s
Figure 8: LTI system.
Y =
_
q(s)
r(s)
_
U
e
st
is an eigenfunction of a LT I system.
eigenvalue (s) =
q(s)
r(s)
(s-dependent) of this eigenfunction. We call
this ratio G(s) or the transfer function.
G(s) U(s) Y(s)
Figure 9: Laplace transfer function
u(t) =

k=1
U
k
e
s
k
t
y(t) =

k=1
Y
k
e
s
k
t
where Y
k
= G(s
k
)U
k
u(t) =
_
u(s)e
st
ds continuous distribution
U(s) =
_

0
u(t)e
st
dt
exists if u(t) is such that there exists some
0
R so that
lim
t
e

0
t
|u(t)| = 0
11
This is a line integral in the complex plane:
u(t) = lim

1
2j
_

0
+j

0
j
U(s)e
st
ds with s =
0
+ j
Fundamental Transforms:
L{f(t)}
_

0
f(t)e
st
dt F(s)
where,
f(t) = e
pt
for any p C
then,
F(s) =
1
s p
if p = 0 : f(t) = e
0t
= 1
t
F(s) =
1
s
In using the unilateral laplace transform, we can assume:
1. f(t)=0
t
< 0
2. lower limit of 0 in the integral is really 0

## , the instant before t = 0

ex:
f(t)=1(t)
t
f(t)=1
1
1(t) ={
0 t<0
1 t0
Figure 10: Step function.
12
ex:
f(t)=e 1(t)
t
f(t)=e
1
p
p < 0
pt
pt
Figure 11: Exponential decay.
f(t) = 2re
t
cos (t + )
where,
r, R
, R
F(s) =
A
s p
+

A
s p
where, A, p C, p = + j, A = re
j
Fundamental Properties
1. Linearity: L{a
1
f
1
(t) + a
2
f
2
(t)} = a
1
F
1
(s) + a
2
F
2
(s)
2. Time Shift: L{f(t )} = e
s
F(s)
3. Dierentiation rule:
L{

f(t)} = sF(s) f(0) (8a)
L{

f(t)} = s
2
F(s) sf(0) f(0) (8b)
where 1b can be obtained via iteration of 1a.
Apply to LT I SISO dierential equation:
y
(n)
(t) +
(n1)
y
(n1)
(t) +. . .
1
y(t) +
0
y(t) =
m
u
(m)
(t) +. . .
1
u(t) +
0
u(t)
13
Laplace transform both sides:
Y (s) = G(s)U(s) +
c(s)
r(s)
where,
G(s) =
q(s)
r(s)
and
q(s) =
m
s
m
+ . . . +
1
s +
0
r(s) = s
n
+
(n1)
s
(n1)
+ . . . +
1
s +
0
c(s) - polynomial determined from inital conditions.
if U(s) is a rational function of s
U(s) =
a(s)
b(s)
a,b both polynomials in s
substituting back in:
Y (s) =
q(s)a(s)
r(s)b(s)
+
c(s)
r(s)
=
q(s)a(s) + c(s)b(s)
r(s)b(s)

N(s)
D(s)
where N,D are polynomials in s.
factor the denominator:
D(s) = r(s)b(s)
where
r(s) =
n

k=1
(s p
k
)
where r(p
k
) = 0 G(p
k
) = ; therefore, p
k
are the poles of G(s).
b(s) =
h

l=1
(s
l
)
14
when b(
l
) = 0
l
are the poles of U(s).
Partial fraction expansion:
Y (s) =
n

k=1
A
k
s p
k
+
L

l=1
B
l
s
l
Residue Formula
A
k
= [(s p
k
)Y (s)]
s=p
k
B
l
= [(s
l
)Y (s)]
s=
l
_
= Assumed no repeated factors in D(s)
y(t) =
n

k=1
A
k
e
p
k
t
. .
y

h
(t)
+
L

l=1
B
l
e

l
t
. .
y

p
(t)
*Depends on both initial conditions and the form of the input!
**This shows why the poles of the input form the forced response!
Note: since r(s), b(s) are polynomials with real coecients, for example,
p
k
=
k
+ j
k
satises r(p
k
) = 0 with
k
= 0, then also p
k
=
k
j
k
satises r( p
k
) = 0. In other words, the poles will occur in complex pairs.
Moreover,
[(s p
k
)Y (s)] =

A
k
i.e. the corresponding partial fraction expansion coecients will also be
complex conjugates.
A
k
s p
k
+

A
s p
k
looks like
2r
k
e

k
t
cos (
k
t +
k
)
where, r
k
= |A
k
|,
k
= A
k
, p
k
=
k
+ j
k
.
15
An important additional engineering test function
t
(t)

(t) =
_
1

0 t
0 otherwise
_

0

## (t)dt = 1 unit area for any

Dene:
(t) = lim
0

(t) =
_
t = 0
0 t = 0
_

0
(t)dt =
_

0
lim
0

(t)dt
= lim
0
_

0

(t)dt = lim
0
_

0
_
1

_
dt = 1
for any > 0
_

0
(t)dt = 1
This is the Dirac delta function and has the sifting property
_

0
(t)f(t)dt = f(0)
for any
_

0
(t )f(t)dt = f()
16
t
(t)
t-
(t-)
Figure 13: Sifting property of the delta function.
recall again Laplace
H(s) = L{h(t)} =
_

0
h(t)e
st
dt
if
h(t) = (t)
then
H(s) =
_

0
(t)e
st
dt = [e
st
]
t=0
= 1
L{(t)} = 1 = (s)
Note:
(t) =
_
(s)e
st
ds
=
_
e
st
ds
17